Central corneal thickness to adjust IOP measurements - A.V. Korneeva; A.V. Kuroyedov; D.N. Lovpache; I.R. Gazizova; S.Yu. Petrov; I.A. Loskutov (РМЖ "Клиническая офтальмология")
A.V. Korneeva1, A.V. Kuroyedov2,3, D.N. Lovpache1, I.R. Gazizova4, S.Yu. Petrov5, I.A. Loskutov6 1LLC “3-Z”, Moscow, Russian Federation 2P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation 4Institute of Experimental Medicine of the Russian Academy of Sciences, St. Petersburg, Russian Federation 5Scientific Research Institute of Eye Diseases, Moscow, Russian Federation 6Department of Ophthalmology, Science Clinical Сenter of Russian Railways, Moscow, Russian Federation This article describes the effect of central corneal thickness (CCT) on intraocular pressure (IOP) measurements. CCT is known to affect applanation tonometry readings thus resulting in late glaucoma diagnosis and inadequate IOP-lowering treatment. In patients with thick cornea, ignoring of this parameter will lead to overdiagnosis and unreasonable therapies. In patients with thin cornea, “understated” IOP levels will lead to late glaucoma diagnosis and incorrect management. Data on CCT as a risk factor for glaucoma development and progression are addressed. The article discusses the effect of CCT on the readings of various methods of tonometry. In advanced glaucoma, CCT significantly reduces, as a result, the proportion of thin corneas increases as compared with early glaucoma. Practical need to measure CCT in the course of standard ocular examination is highlighted. However, until recently, the standards of IOP re-calculation adjusted for CCT are not deter mined yet thus requiring further studies. Keywords: glaucoma, intraocular pressure, tonometry, central corneal thickness, corneal hysteresis. For citation: Korneeva A.V., Kuroyedov A.V., Lovpache D.N. et al. Central corneal thickness to adjust IOP measurements. Russian Journal of Clinical Ophthalmology. 2020;20(1):–20. DOI: 10.32364/2311-7729-2020-20-1-15-20.